2021
DOI: 10.3389/froh.2021.686863
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Deep Machine Learning for Prognostication of Oral Squamous Cell Carcinoma—A Systematic Review

Abstract: The application of deep machine learning, a subfield of artificial intelligence, has become a growing area of interest in predictive medicine in recent years. The deep machine learning approach has been used to analyze imaging and radiomics and to develop models that have the potential to assist the clinicians to make an informed and guided decision that can assist to improve patient outcomes. Improved prognostication of oral squamous cell carcinoma (OSCC) will greatly benefit the clinical management of oral c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 61 publications
(180 reference statements)
0
28
0
Order By: Relevance
“…Of the 7 included systematic reviews [ 7 , 18 23 ], 4 were conducted in Asia (i.e., 2 each from China and India) [ 18 , 19 , 21 , 22 ] while 2 reviews was conducted in Europe (Finland) [ 7 , 23 ] and one review in the United States [ 20 ] ( Table 2 ). The quality appraisal for all the review papers considered in this study indicated that 42.9% showed high quality [ 7 , 21 , 22 ] while 57.1% showed medium quality [ 18 20 , 23 ]. Three of the reviews were conducted in the year 2020 [ 18 20 ] while four were conducted in the year 2021 [ 7 , 21 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the 7 included systematic reviews [ 7 , 18 23 ], 4 were conducted in Asia (i.e., 2 each from China and India) [ 18 , 19 , 21 , 22 ] while 2 reviews was conducted in Europe (Finland) [ 7 , 23 ] and one review in the United States [ 20 ] ( Table 2 ). The quality appraisal for all the review papers considered in this study indicated that 42.9% showed high quality [ 7 , 21 , 22 ] while 57.1% showed medium quality [ 18 20 , 23 ]. Three of the reviews were conducted in the year 2020 [ 18 20 ] while four were conducted in the year 2021 [ 7 , 21 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of the 7 included systematic reviews [7,[18][19][20][21][22][23], 4 were conducted in Asia (i.e., 2 each from China and India) [18,19,21,22] while 2 reviews was conducted in Europe (Finland) [7,23] and one review in the United States [20] (Table 2). The quality appraisal for all the review papers considered in this study indicated that 42.9% showed high quality [7,21,22] while 57.1% showed medium quality [18][19][20]23]. Three of the reviews were conducted in the year 2020 [18][19][20] while four were conducted in the year 2021 [7,[21][22][23].…”
Section: Characteristics Of Relevant Studiesmentioning
confidence: 99%
See 3 more Smart Citations